Superconductivity in S-rich phases of lanthanum sulfide under high pressure - Gao, Kun; Cui, Wenwen; Wang, Qinfang; Hao, Jian; Shi, Jingming; Botti, Silvana; Marques, Miguel A. L.; Li, Yinwei (Physical Review Materials, 2022)
Pressure, a fundamental thermodynamic variable, enables phase transitions to exotic phases with unique physical properties, such as superconductivity. In this work we perform a complete study of crystal structures and relevant electronic properties of La-S crystalline systems in a pressure range of 0-200 GPa. A structural search based on first-principles swarm-intelligence identifies two hitherto unknown pressure-stabilized stoichiometries, namely, LaS3 and LaS5, in addition to the previously reported compounds. We find that the S-S bonding patterns in La-S compounds evolve in the following sequence with increasing S content and pressure: Atomic S, S2 dimers, one-dimensional linear S chains, and two-dimensional S ladders. Further electron-phonon calculations show that both LaS3 and LaS5 are superconductors with critical temperatures of 13.6 K at 100 GPa and 11 K at 120 GPa, respectively. The softened acoustic phonon branches are responsible for their superconductivity. Our current work is expected to guide future experimental studies investigating superconductivity and structural features of La-S system and more, in general, of other rare-earth chalcogenides.
CRIS-Team Scopus Importer:2023-04-20